Trains Detection Using LTE Downlink Reference Signals - Olga Blaszkiewicz; Krzysztof K. Cwalina; Alicja Olejniczak; Piotr Rajchowski; Jaroslaw Sadowski (IEEE Access)
In this article a method for detecting the presence of trains on tracks by analyzing the changes in the cell-specific reference symbols parameters in the downlink signal from nearby LTE base station operating in transmit diversity mode is proposed. The signal processing method to obtain waveforms showing correlation with the presence of trains is described with experimental results on trains detection using real LTE downlink signals from commercial networks. The main outcome of the investigation is that even in case of signal reception using receiver with limited long term stability, which doesn’t allow to track absolute phase values of reference symbols, difference between received phases of symbols transmitted using different antenna ports in base station may be highly correlated with presence of trains on tracks. Proposed reference symbols analysis may be alternative to detection of objects in the environment using bistatic passive radar principle, which couldn’t be used in proposed measurement setup due to low performance of bistatic radar detection using single antenna receiver.